IDENTIFIKASI STRATEGI LOW COST YANG DITERAPKAN PERUSAHAAN STUDI KASUS PADA PT.MADUBARU - Kartika Pradana Suryatimur (Master in Accounting Program, 2018)
Good strategy determination compared to competitors will provide acompetitive advantage and improve the profitability of the company. The nationalsugar industry is in decline demanding that producer companies must implementthe right strategy to survive in the industry. Sugar is a standard product socompanies apply low cost strategies.PT Madubaru is one of the sugar producers, implementing low cost strategyin its business activities. This study analyzes the management policy on investmentsmade by companies from 2007 to 2016. The results of management policy analysiscan be known how PT Madubaru implemented a strategy to compete in the sugarindustry. PT. Madubaru increased production capacity by investing in newmachines that have larger capacity than before.The result of the research shows that the management policy on theinvestment made by the company fails to reduce the production cost. This is becausethe increase in production capacity is not followed by the availability of sugarcaneraw materials, causing idle capacity.